DIODE LASER EXCISION OF A FIBROUS EPULIS IN AN ORTHODONTIC PATIENT. CASE REPORT - Maria-Alexandra Martu; George-Alexandru Maftei; Irina-Georgeta Sufaru; Ioana-Andreea Sioustis; Diana-Cristala N; Carmen Savin; Ioana Martu; Ionut Luchian (Romanian Dental Association for Education, 2020)
Lasers are used in oral surgery and periodontology liberally nowadays, however, solid therapeutic protocols are still lacking in some medical areas. An epulis is defined clinically as hyperplasia of the gingival tissues, usually situated in the proximity of the interdental papilla, however it may also occur in the edentulous ridges. Regarding the origin of this particular lesion the periodontun and the periosteum are considered principal components. In this case report we present an orthodontic patient with a recurrent fibrous epulis that was treated by ablation with a diode laser (940nm). This particular method was chosen due to the reduced treatment time and diminished intrasurgical bleeding. Furthermore, an improved gingival healing compared with classical scalpel blade surgical treatment was observed. We demonstrated that diode lasers are particularly useful tools in orthodontic patients that are predisposed to gingival hyperplasia and this treatment method has supplementary advantages compared to the classical scalpel regarding the presence and intensity of pain and postoperative discomfort